ESHRE PGD Consortium data collection XIV–XV: cycles from January 2011 to December 2012 with pregnancy follow-up to October 2013. Issue 10 (30th August 2017) - De Rycke, M; Goossens, V; Kokkali, G; Meijer-Hoogeveen, M; Coonen, E; Moutou, C
Abstract: STUDY QUESTION: How does the data collection XIV–XV of the European Society of Human Reproduction and Embryology (ESHRE) PGD Consortium compare with the cumulative data for data collections I–XIII? SUMMARY ANSWER: The 14th and 15th retrospective collection represents valuable data on PGD/PGS cycles, pregnancies and children: the main trend observed is the increased application of array technology at the cost of FISH testing in PGS cycles and in PGD cycles for chromosomal abnormalities. WHAT IS KNOWN ALREADY: Since 1999, the PGD Consortium has collected, analysed and published 13 previous data sets and an overview of the first 10 years of data collections. STUDY DESIGN, SIZE, DURATION: Data were collected from each participating centre using a FileMaker Pro database (versions 5–12). Separate predesigned FileMaker Pro files were used for the cycles, pregnancies and baby records. The study documented cycles performed during the calendar years 2011 and 2012 and follow-up of the pregnancies and babies born which resulted from these cycles (until October 2013). PARTICIPANTS/MATERIALS, SETTINGS, METHOD: Data were submitted by 71 centres (full PGD Consortium members). Records with incomplete or inconsistent data were excluded from the calculations. Corrections, calculations and tables were made by expert co-authors. MAIN RESULTS AND THE ROLE OF CHANCE: For data collection XIV–XV, 71 centres reported data for 11 637 cycles with oocyte retrieval (OR), along with details of the follow-up on 2147 pregnancies and 1755 babies born. A total of 1953 cycles to OR were reported for chromosomal abnormalities, 144 cycles to OR for sexing for X-linked diseases, 3445 cycles to OR for monogenic diseases, 6095 cycles to OR for PGS and 38 cycles to OR for social sexing. From 2010 until 2012, the use of arrays for genetic testing increased from 4% to 20% in PGS and from 6% to 13% in PGD cycles for chromosomal abnormalities; the uptake of biopsy at the blastocyst stage (from <1% up to 7%) was only observed in cycles for structural chromosomal abnormalities, alongside the application of array comparative genomic hybridization. LIMITATIONS, REASONS FOR CAUTION: The findings apply to the 71 participating centres and may not represent worldwide trends in PGD. WIDER IMPLICATIONS OF THE FINDINGS: The annual data collections provide an important resource for data mining and for following trends in PGD/PGS practice. STUDY FUNDING/COMPETING INTEREST(S): None.